Comparison Of Web Load Speed Between Babel Transpiler and SWC On Website-Based Applications - Rangga Prasetya, Rangga Prasetya; Sujatmiko, Bambang (Universitas Negeri Surabaya, 2025)
Transpilers play an important role in software development by translating code from one programming language to another, allowing developers to take advantage of modern features and capabilities without having to change the entire project. For example, by using a transpiler like Babel, developers can write the latest JavaScript code that remains compatible with older browsers, similar to translating a book into multiple languages ​​to make it accessible to a wider audience. Babel is the most commonly used transpiler. On the other hand, there is SWC which is a new transpiler that is claimed to be faster than Babel. This study aims to determine the difference in the speed of the Babel and SWC transpilers. The data for this study were taken from several pages using Google Lighthouse. The data were analyzed using a parametric test, namely the paired sample t-test. The results of the study showed that SWC had a significant difference in speed compared to Babel in the First Contenfulpaint (FCP) and Speed ​​​​Index (SI) indicators. Babel is superior in Total Blocking Time (TBT). While in the Largest Contenfulpaint (LCP), Babel is significantly superior to SWC. This shows that SWC is faster than Babel transpiler in web load speed because in the speed indicators, namely FCP and SI, SWC is significantly superior.